Chemical Mechanical Surface Nano-Structuring (CMNS) Implementation on Titanium Based Implants to Enhance Corrosion Resistance and Control Biocompatibility. (2020) - Beers, Kimberly; Sur, Debashish; Basim, G. Bahar
Abstract: Titanium is the metal of choice for many implantable devices including dental prostheses, orthopaedic devices and cardiac pacemakers. Titanium and its alloys are favoured for hard tissue replacement because of their high strength to density ratio providing excellent mechanical properties and biocompatible surface characteristics promoting in-vivo passivation due to spontaneous formation of a native protective oxide layer in the presence of an oxidizer. This study focuses on the development of a three-dimensional chemical, mechanical, surface nano-structuring (CMNS) process to induce smoothness or controlled nano-roughness on the bio-implant surfaces, particularly for applications in dental implants. CMNS is an extension of the chemical mechanical polishing (CMP) process. CMP is utilized in microelectronics manufacturing for planarizing the wafer surfaces to enable photolithography and multilayer metallization. In biomaterials applications, the same approach can be utilized to induce controlled surface nanostructure on three-dimensional implantable objects to promote or demote cell attachment. As a synergistic method of nano-structuring on the implant surfaces, CMNS also makes the titanium surface more adaptable for the bio-compatible coatings as well as the cell and tissue growth as demonstrated by the electrochemical and surface wettability evaluations on implants prepared by DI-water machining versus oil based machining.